LESSON PLAN DEVELOPMENT BASED ON CHARACTER FOR THE TENTH GRADE STUDENTS OF VOCATIONAL SCHOOL - Putra, B.M. (Universitas Pendidikan Ganesha, 2017)
This study was a Research and Development study (R&D) used Sugiyonoâs model which aimed at (1) analyzing the design of the existing English lesson plans in SMK Triatma Jaya Singaraja, (2) identifying the problems faced by the English teacher in designing good English lesson plans (3) determining the good design of Character Based English Lesson Plans in SMK Triatma Jaya Singaraja (4) determining the quality of the Character Based Lesson Plans developed. The data of the present study were analyzed descriptively and quantitatively. This result showed that the existing lesson plans did not clearly state the values of nation character and the assessment and it was not explicitly stated on the learning activity. The learning activity seemed monotone. There seemed to be materials repetition. The materials must be suitable with the studentsâ department. The lesson plans developed were designed based on technical guideline of lesson plan development proposed by Board Directors of Senior High School Development (2010) with character assessment as an addition. The lesson plans were developed in form of integrated lesson plan. The lesson plans developed were effective and the quality is excellent.